1991
DOI: 10.1128/aem.57.10.3006-3012.1991
|View full text |Cite
|
Sign up to set email alerts
|

NH 4 + -Excreting Azospirillum brasilense Mutants Enhance the Nitrogen Supply of a Wheat Host

Abstract: Spontaneous ethylenediamine-resistant mutants of Azospirillum brasilense were selected on the basis of their excretion of NH4'. Two mutants exhibited no repression of their nitrogenase enzyme systems in the presence of high (20 mM) concentrations of NH4'. The nitrogenase activities of these mutants on nitrogen-free minimal medium were two to three times higher than the nitrogenase activity of the wild type. The mutants excreted substantial amounts of ammonia when they were grown either under oxygen-limiting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Considering the intracellular presence of this nitrogenated material, including a possible protein reserve, the present study supports the hypothesis proposed by Yahalom et al (1984) and by Christiansen-Weniger and Van Veen (1991). Accordingly, free-living, diazotrophic microorganisms may contribute nitrogen to the environment, in the form of decomposed bacterial structures.…”
Section: Resultssupporting
confidence: 91%
“…Considering the intracellular presence of this nitrogenated material, including a possible protein reserve, the present study supports the hypothesis proposed by Yahalom et al (1984) and by Christiansen-Weniger and Van Veen (1991). Accordingly, free-living, diazotrophic microorganisms may contribute nitrogen to the environment, in the form of decomposed bacterial structures.…”
Section: Resultssupporting
confidence: 91%
“…However, reports of other researchers showed that IAA production was not detected after 5 d. Though it is reported that there is continuous decrease in IAA production after reaching the peak production, this pattern was also followed by our isolates. IAA production curves of the isolates showed continuous increase and decrease up to 12 d. These types of curves are in agreement with the IAA production curves reported by Torres-Rubioet al [26,27]. The reason for such fluctuations could be the utilization of IAA by the cells as nutrient during late stationary phase or production of IAA degrading enzymes by the cells which are inducible enzymes in presence of IAA [26].…”
Section: Indole Acetic Acid Productionsupporting
confidence: 89%
“…Anabaena mutants resistant to L-methionine-DL-sulfoximine or the NH4' analog ethylenediamine excreted up to 1.6 mM NH4' (35,43,45). Among eubacteria, ammonium excretion was reported to occur in mutants of Klebsiella pneumoniae defective in ammonium assimilation or transport (1,8,41), in mutants of Rhodobacter capsulatus and Azospirillum brasiliense altered in the production of GS (27,48), in methylamine-resistant mutants of Azotobacter vinelandii (17), and in ethylenediamine-resistant mutants of A. brasiliense (9,27).…”
mentioning
confidence: 99%